Reacting to unexpected losses in an uncertain world: High approach individuals become even more risk-seeking. (15th April 2017) - Tan, Xiaoyue; Van Prooijen, Jan-Willem; Proulx, Travis; Wu, Haizheng; Van Beest, Ilja; Van Lange, Paul A.M.
Abstract: Previous research has shown that people are risk-seeking in the face of losses. We propose that this risk-seeking orientation is a palliative approach response to deal with a discrepancy between people's desire to avoid losses versus the possibility of loss. An expectancy violation (which induces behavioral approach responses) would therefore strengthen people's risk-seeking in the context of losses. Two experiments (Study 1 and Study 2) which were conducted in the context of the Asian Disease Problem demonstrated that people high in trait behavioral approach (trait BA) were more risk-seeking following an expectancy violation (state BA) than in a control condition. As expected, this was only the case for decisions framed in terms of losses, but not in terms of gains (Study 1). Taken together, our findings highlight the interacting motivational influences of situation-induced state behavioral approach and trait behavioral approach in understanding risky decision-making in the face of losses. Highlights: People are more risk-seeking in the domain of losses than in the domain of gains. Risk-seeking in losses is subject to a behavioral approach motivation. Expectancy violation triggers more risk-seeking in losses for high approach people. These findings illuminate the motivational accounts for risk seeking in losses.